2011
DOI: 10.1108/09727981111129354
|View full text |Cite
|
Sign up to set email alerts
|

Productivity‐based hybrid model: learning from the Indo‐Japanese and Indian auto sector

Abstract: PurposeIn the rapidly changing market and environment, companies need to employ highly competitive human resources for sustaining a competitive advantage. Human resource management (HRM) practices have a significant impact on firm performance. The purpose of this paper is to identify the key HRM factors from a survey of 41 Indo‐Japanese and 35 Indian firms operating in Delhi and the National Capital Region (NCR) (India) in the automobile sector that affect the productivity and overall performance of firms.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Gupta and Prasad (2011) examined a survey of 76 Indian-Japanese and Indian manufacturing facilities to find the HRM factors that affect productivity and overall firms’ performance. The authors used factorial analysis to examine the various HRM factors that affect the organizations’ productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gupta and Prasad (2011) examined a survey of 76 Indian-Japanese and Indian manufacturing facilities to find the HRM factors that affect productivity and overall firms’ performance. The authors used factorial analysis to examine the various HRM factors that affect the organizations’ productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that talent planning and engagement, talent motivations, and assessment training needs are common factors that affect productivity in both Indian-Japanese and Indian facilities. However, service training and talent acquisition are only significant for Indian-Japanese and Indian, respectively (Gupta and Prasad, 2011). Even though surveys have several advantages, their validity can sometimes be a real issue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gupta and Prasad’s (2011) study has identified factors like job rotation, in-service training and requisite qualifications besides teamwork, compensation, participation in decision making and performance appraisal significantly impact productivity of Indian and Indo-Japanese firms in automobile sectors. However, Indian firms need to accord greater emphasis to in-house training, compared to the Japanese ventures (p. 168).…”
Section: Strategic Nature Of Learning Functionmentioning
confidence: 99%
“…Findings of Singh's (2004) study, conducted across 82 Indian firms, revealed that there is a significant relationship between the two human resources practices, namely, training and compensation, and perceived organizational and market performance of the firm. Gupta and Prasad's (2011) study has identified factors like job rotation, inservice training and requisite qualifications besides teamwork, compensation, participation in decision making and performance appraisal significantly impact productivity of Indian and Indo-Japanese firms in automobile sectors. However, Indian firms need to accord greater emphasis to in-house training, compared to the Japanese ventures (p. 168).…”
mentioning
confidence: 99%
“…They found that talent planning and engagement, talent motivations, and assessment training needs are common factors that affect productivity in both Indian-Japanese and Indian facilities. However, service training and talent acquisition are only significant for Indian-Japanese and Indian, respectively (Gupta &Prasad, 2011). Even though, surveys have several advantages, their validity can sometimes be a real issue.…”
Section: Studies That Have Been Done To Improve Productivitymentioning
confidence: 99%